The emergence of multidrug-resistant acinetobacter baumannii in colombia: a time-series analysis, 2001-2007 (2011)
Objective This study was aimed at analyzing the phenotypical behavior of Acinetobacter baumannii resistance to antibiotics currently available in Colombia for its treatment. Methods An ecological time-series study was conducted based on information regarding A. baumannii resistance to available antibiotics gathered through a Colombian surveillance system involving 33 reference hospitals. Descriptive analysis and modeling forecasting were also carried out. Results The sample included 5.415 A. baumannii isolates collected from 33 hospitals throughout Colombia. This microorganism was the eighth most frequently isolated pathogen in hospital settings, having 3.8 % isolation frequency in intensive care units (ICUs).The study recorded the presence of multidrug-resistant A. baumannii strains since 2001, as well as a dramatic increase in A. baumannii strains having decreased susceptibility to the antibiotics currently available on the market (30 % to 70 %). Conclusion A. baumannii has shown a clear transition to a multidrug resistance profile in Colombia during recent years which includes resistance to important secondline antibiotics, such as carbapenems.